Analisis Faktor-Faktor Terkait Akses Usia Produktif (15-64 Tahun) di Wilayah Kerja Puskesmas Kota Kutacane Pulonas, Kecamatan Babussalam, Kabupaten Aceh Tenggara - Halimatussakdiyah Lubis; Yusnaini Yusnaini (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Health service facilities are all facilities and infrastructure tools or places that can support health or can be used to provide health services, both promotive, preventive, curative and rehabilitative carried out by the government, local governments and / or the community, (Ministry of Health RI, 2016). The research design was described using a cross-sectional research design. The research was conducted in the working area of the Kutacane Pulonas City Health Center, Babussalam District, Southeast Aceh Regency. The population of this study was the entire population of productive age who visited the Kutacane City Health Center. The sample for the study was 127 respondents, a sampling of the general population. The data analysis carried out was univariate and bivariate analysis. From the results of the study, it is known that the factors that influence low access show that access to productive age people in the working area of the Kutacane City Health Center is influenced by gender, marital status, knowledge, attitudes, cadre support, facilities and infrastructure, information about the schedule for implementing health screening, and satisfaction with productive age health services.